2011
DOI: 10.1126/scitranslmed.3002788
|View full text |Cite
|
Sign up to set email alerts
|

dbGaP Data Access Requests: A Call for Greater Transparency

Abstract: The scientific and public health benefits of mandatory data-sharing mechanisms must be actively demonstrated. To this end, we manually reviewed 2724 data access requests approved between June 2007 and August 2010 through the U.S. National Center for Biotechnology Information (NCBI) database of genotypes and phenotypes (dbGaP). Our analysis demonstrates that dbGaP enables a wide range of secondary research by investigators from academic, governmental, and nonprofit and for-profit institutions in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…In a 2011 commentary based on the National Center for Biotechnology Information Database of Genotypes and Phenotypes (dbGaP), Walker et al reported on activities during the 2007–2010 period and included 2724 data-access requests from 851 investigators. 16 The principal reason for dbGaP requests involved exploration of new association analysis (39%), followed by methodologic research (26%), replication (18%), and control groups (11%). The dbGaP summary, however, was unable to link requests to subsequent publications.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2011 commentary based on the National Center for Biotechnology Information Database of Genotypes and Phenotypes (dbGaP), Walker et al reported on activities during the 2007–2010 period and included 2724 data-access requests from 851 investigators. 16 The principal reason for dbGaP requests involved exploration of new association analysis (39%), followed by methodologic research (26%), replication (18%), and control groups (11%). The dbGaP summary, however, was unable to link requests to subsequent publications.…”
Section: Discussionmentioning
confidence: 99%
“…1 One component of NIH policy is the expectation that data from certain types of NIH-funded genetic studies will be deposited into a federal data repository, dbGAP, for sharing with other researchers. 2,3 Once data are submitted to dbGAP, an NIH Data Access Committee consisting of federal employees, reviews researcher applications for data use and determines access based on scientific merit and consistency of proposed research with limitations imposed on the dataset (e.g., scope of informed consent). Requests for dbGAP access largely come from the research community, including academic institutions, governmental, for-profit and nonprofit institutions.…”
mentioning
confidence: 99%
“…Requests for dbGAP access largely come from the research community, including academic institutions, governmental, for-profit and nonprofit institutions. 3 This approach, and data sharing more generally, has the goal of increasing the efficiency of the research process and promoting public benefit by maximizing the use of a pooled data resource for future studies. It is viewed as a particularly important tool for genomic research, enabling more rapid development of health-related advances.…”
mentioning
confidence: 99%
“…We are also beginning to use natural language processing technology from the National Library of Medicine to index text documents and to remove personal identifiers. [50] The priorities in which we take on these new projects are set by our user community; the rate at which they are achieved are based on the availability of funding resources.…”
Section: Discussionmentioning
confidence: 99%